Q: Simplify the answer of 4a plus b-2a-2b?

Write your answer...

Submit

Related questions

5x - 8a + 4a - 2x + a = 3x - 3a

3a * * * * * Actually, it is 4a.

2a+6b

11a+7b-(3b-2a)

4a+5=25 4a=25-5 4a=20 a=20/4 a=5

3a - 2b

Add them together: 3a+4a-a = 6a

It is -44 + 4a

6a - 8 - 4a - 2 → 6a - 4a - 8 - 2 → 2a - 10

7

The answer to 4a times 3b equals 1.3. You have to find the value of A and B.

no

48a3 + 32a2 + 4a = 4a(12a2 + 8a + 1)

Without any signs between what appear to be terms, it is not possible to simplify.

a2 - 4a + 4

21a - 6a

2b+b-4

You need to combine the different parts that contain the variable "a". Just add the coefficients together algebraically.

5ab-2ab+4a-b+5b = 3ab+4a+4b

If the question was 3a + 4a - a, the answer is 6a. If the question was something else please resubmit using words eg "plus", "divide", "equals" because the browser used for posting questions does not like symbols!

10a + 3a - 4a = 9a

is that ment to be a > sign? well if it is3a>4a-5 (-4a)-a>-5 then just inverta>5

It is an expression of two terms as: 4a+12

"a" plus "3a" is equal to 4a. (3a+a=4a). You already have 3 "a's" and then you add another "a."

58

Study guides